Natural history of gastrointestinal manifestations in vascular Ehlers–Danlos syndrome: A 17‐year retrospective review. Issue 5 (20th November 2018) - Frank, Michael; Adham, Salma; Zinzindohoué, Franck; Jeunemaitre, Xavier
Abstract: Background and Aim: Vascular Ehlers–Danlos syndrome (vEDS) is a rare connective tissue disorder due to heterozygous mutations in the COL3A1 gene with a dominant negative effect. Spontaneous bowel perforation and intra‐abdominal organ rupture are common complications of vEDS. Other gastrointestinal (GI) manifestations may occur but have not been extensively characterized. We herein describe the natural history of GI events and surgery‐related complications in patients with vEDS. Methods: A retrospective review of GI events in a large cohort of molecularly proven vEDS patients was conducted, after exclusion of mild forms of the disease. Results: Of 133 patients, 41% had a history of GI manifestations with 112 events, mean 2.0 ± 1.3 events per patient. There was an earlier occurrence of GI events in men ( P 0.008). Cumulative incidence was 58% for all patients, higher in men and in patients with splice‐site variants. Recurrence of GI events was reported in more than 50% of patients. Colonic perforation was the first digestive event for 47% of patients. Of 85 GI surgeries, 37 (43%) were complicated with 43 events. Nine deaths were reported in this population. Conclusions: Vascular Ehlers–Danlos syndrome is characterized not only by bowel perforation but also by a wide variety of GI complications that occur in close to half (41%) of patients. The pattern of GI fragility seems more severe in males and splice‐site variants. Complications of GI surgery are common and are related with tissue fragility/friability.